The role of adiwiyata school in the change of students' knowledge, attitude, and behavior towards the environment - Siti Badriyah Rushayati; Rachmad Hermawan; Lin Nuriah Ginoga (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Environmental problems and their solutions must be introduced to students from an early age through Environmental Education (PLH). One of PLH’s implementations is the Adiwiyata Program. The success of the Adiwiyata Program can be measured by examining differences in knowledge, positive attitudes, and positive behavior towards environmental problems and solutions. This study aimed to analyze quantitatively and qualitatively differences in knowledge, positive attitudes and positive behavior regarding the environment in school that has participated and that who has not participated in the Adiwiyata Program. Data were analyzed using a Likert scale with three categories: 1) good, 2) quite good, and 3) not good. Mann-Whitney U Test analysis was conducted to test the significance of the difference between the two groups of respondents. There was a difference in knowledge, attitudes, behavior and PLH scores in school that has participated in the Adiwiyata Program and that who has not. There was also a difference in student knowledge but not significant between schools participating in the Adiwiyata Program and not participating in the program. Students who participated in the Adiwiyata Program had better PLH scores than those who did not follow the Adiwiyata program